Zakat Management Information System: E-Service Quality and Its Impact on Zakat Collection in Indonesia - Randi Swandaru (International Journal of Zakat, 2019)
The purpose of this study is to examine the impact and the electronic service quality of the national zakat management information system (SIMBA) on the national zakat collection. This paper uses a multiple regression analysis in its explorative attempt to illustrate the impact of SIMBA implementation on zakat collection in Indonesia. It shows that SIMBA is positive and significantly impact the national zakat collection as well as the human development index that is used as a proxy for the human resource management quality of zakat institutions. Nonetheless, the population is negative and significant to the zakat collection as endemic poverty and reluctance to pay zakat are indicated as the reasons. Moreover, this study has succeeded in adapting and conducting an e-service quality survey to zakat information system realm. All the tests prove that the instrument in this study has a high degree of reliability and validity. The results show that some of the demographic factors significantly impact the perceived performance of SIMBA. Multiple regression analysis that is conducted in this study shows that e-service quality dimension is positive and significant towards SIMBA’ overall quality, perceived value, and loyalty intention. This study contributes to the zakat literature, especially in the impact of the national zakat information system, which is pivotal in enhancing zakat collection and poverty alleviation program funded by zakat.